Compositional Shift of Oral Microbiota Following Surgical Resection of Tongue Cancer - Kageyama, Shinya; Nagao, Yuka; Ma, Jiale; Asakawa, Mikari; Yoshida, Ryoji; Takeshita, Toru; Hirosue, Akiyuki; Yamashita, Yoshihisa; Nakayama, Hideki (Frontiers in Cellular and Infection Microbiology, 2020)
Salivary microbiota is considered a source of microorganisms for the respiratory and digestive tracts, and a trigger for diseases in these distant organs. Meanwhile, the microbiota on the tongue surface is thought to be a major source of salivary microbiota. Therefore, surgical resection of the tongue for definitive treatment of oral cancer could drastically change the salivary bacterial balance and virulence. Here, we investigated the shift of the salivary microbiota following surgical resection in patients with tongue cancer. The stimulated saliva samples were collected from 25 tongue cancer patients pre- and post-resection of the tongue, and bacterial density and composition was determined using quantitative PCR analysis and 16S ribosomal RNA (rRNA) gene sequencing, respectively. Although no significant difference in the total bacterial density in saliva pre- and post-surgery was observed, the bacterial composition significantly differed according to the analysis of similarity. Among predominant operational taxonomic units (OTUs) with ≥1% of relative abundance, the proportions of OTUs corresponding to Streptococcus salivarius, Prevotellamelaninogenica, and Prevotellahisticola were significantly decreased following the tongue resection. On the other hand, the proportions of OTUs corresponding to Lautropiamirabilis, Neisseriaflava, Streptococcussanguinis, and Fusobacterium nucleatum, known to be inhabitants of dental plaque, were significantly increased. These results suggest that surgical resection of the tongue causes a compositional shift of the salivary microbiota, characterized by an increase in bacterial species derived from dental plaque, including periodontal pathogens. These results suggest the necessity of more careful and frequent postoperative oral care after surgical resection of tongue cancer.